Pseudomonas aeruginosa Exoenzyme S Stimulates Murine Lymphocyte Proliferation In Vitro - Barclay, Neil G. (American Society for Microbiology, 1999)
The exuberant immunoinflammatory response that is associated with Pseudomonas aeruginosa infection is the major source of the morbidity and mortality in cystic fibrosis (CF) patients. Previous studies have established that an exoproduct of P. aeruginosa (exoenzyme S) is a mitogen for human T lymphocytes and activates a larger percentage of T cells than most superantigens, which may contribute to the immunoinflammatory response. An animal model would facilitate studies of the pathophysiologic consequences of this activation. As a first step toward developing an animal model, the murine lymphocyte response to exoenzyme S was examined. When stimulated with exoenzyme S, splenocytes isolated from naive mice entered S phase and proliferated. The optimum response occurred after 2 to 3 days in culture, at 4 × 10(5) cells per well and 5.0 μg of exoenzyme S per ml. The response was not due to lipopolysaccharide, since Rhodobacter sphaeroides lipid A antagonist did not block the response. Other preparations of exoenzyme S stimulated lymphocyte proliferation, since the response to recombinant exoenzyme S (rHisExo S) cloned from strain 388 was similar to the response to exoenzyme S from strain DG1. There was evidence that genetic variability influenced the response, since A/J, CBA/J, and C57BL/6 mice were high responders and BALB/cJ mice were low responders following stimulation with exoenzyme S. Both splenic T and B lymphocytes entered the cell cycle in response to exoenzyme S. Thus, murine lymphocytes, like human lymphocytes, respond to P. aeruginosa exoenzyme S, which supports the development of a murine model that may facilitate our understanding of the role that exoenzyme S plays in the pathogenesis of P. aeruginosa infections in CF patients.